Isolation and characterization of a surfactant-stable protease from halophilic bacteria Chromohalobacter Japonicus BK-AB18 - Achmad, Dwi Isyana; Ihsanawati; Hertadi, Rukman (Penerbit Universiti Kebangsaan Malaysia, 2020)
The protease from Chromohalobacter japonicus BK-AB18 was produced by growing bacteria in a LB medium containing 5% casein and 5% NaCl. The crude protease was partially purified by three levels of ammonium sulfate concentration (ranges of 0–70%, 70–75% and 75–80%) and the highest specific activity was exhibited in the range of 75–80%. The enzyme has a relative molecular weight of 65 kDa. The protease in this fraction had the highest activity in the following optimum conditions: 7.5% NaCl, a pH of 9.0 and a temperature of 45°C. The activity of the enzyme at the optimum pH and temperature was enhanced by the addition of a Ca2+ ion, but its activity was significantly inhibited by EDTA, hence this enzyme is included as metalloenzyme. Interestingly, the protease activity increased when exposed to a concentration of 0.01% and 0.05% SDS, and was relatively stable in this solution up to a concentration of 10%. It is thus demonstrated that C. japonicus BK-AB18 is a potential source to produce extracellular protease that can be applied in the surfactant/detergent industry.